Beneficios del manejo quirúrgico vs. manejo conservador en fracturas de tercio medio de clavícula - Salas Contreras, Raquel Patricia (2022)
Clavicle fractures represent one of the main injuries of the shoulder girdle in young adults. Its management for years has been conservative; however, new surgical techniques have emerged as well as clinical findings that generate the need to analyze the risks and benefits of the management.   It is essential to individualize each case, taking into account the patient's comorbidities as well as the range of baseline functionality and the patient's wishes.